2018
DOI: 10.1177/0363546518787515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Decellularized Bovine Tendon Sheets for Achilles Tendon Defect Reconstruction in a Rabbit Model

Abstract: DBTSs could serve as an effective bioscaffold to reconstruct AT defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Controlling the macrophage polarization by manipulating the nanomorphology of biomaterial surface may be an effective way to improve the performance of biomaterials ( Ma et al, 2014 ). MSCs exosomes-mediated response in cartilage repair was also found to be associated with regenerative M2 macrophages ( Zhang C.H. et al, 2018 ).…”
Section: Role Of Macrophages In Ecm-mediated Tissue Regenerationmentioning
confidence: 99%
“…Controlling the macrophage polarization by manipulating the nanomorphology of biomaterial surface may be an effective way to improve the performance of biomaterials ( Ma et al, 2014 ). MSCs exosomes-mediated response in cartilage repair was also found to be associated with regenerative M2 macrophages ( Zhang C.H. et al, 2018 ).…”
Section: Role Of Macrophages In Ecm-mediated Tissue Regenerationmentioning
confidence: 99%
“…Although the mechanism of tendon graft repair is poorly understood, adhesion formation with autografts is believed to arise from intrinsic (tenocyte necrosis) and extrinsic fibrosis (influx of synovial and inflammatory cells), leading to excessive scarring [59,76,77]. Other research reported minimal formation of adhesion using acellular allografts on bovine flexor tendon repair [78,79] indicating that acellular allografts can heal without the intrinsic healing mechanism, often observed in autograft tissue.…”
Section: Graft Transplantation Techniquesmentioning
confidence: 99%
“…Techniques usually combine a biomimetic scaffold with biological factors, such as cells and growth factors to provide physical and biochemical cues for tissue growth [65]. Scaffolds obtained from decellularized sources (e.g., human [66,67], porcine [68], canine [69], bovine [70] and equine) are used; however, required donor tissues have weaker mechanical properties and are associated with a high risk of immunogenicity [71,72].…”
Section: Biomimicry Of Soft Tissuesmentioning
confidence: 99%